Reprogramming of Cell Fate During Root Regeneration by Transcriptional and Epigenetic Networks - Jing, Tingting; Ardiansyah, Rhomi; Xu, Qijiang; Xing, Qian; Müller-Xing, Ralf (Frontiers in Plant Science, 2020)
Many plant species are able to regenerate adventitious roots either directly from aerial organs such as leaves or stems, in particularly after detachment (cutting), or indirectly, from over-proliferating tissue termed callus. In agriculture, this capacity of de novo root formation from cuttings can be used to clonally propagate several important crop plants including cassava, potato, sugar cane, banana and various fruit or timber trees. Direct and indirect de novo root regeneration (DNRR) originates from pluripotent cells of the pericycle tissue, from other root-competent cells or from non-root-competent cells that first dedifferentiate. Independently of their origin, the cells convert into root founder cells, which go through proliferation and differentiation subsequently forming functional root meristems, root primordia and the complete root. Recent studies in the model plants Arabidopsis thaliana and rice have identified several key regulators building in response to the phytohormone auxin transcriptional networks that are involved in both callus formation and DNRR. In both cases, epigenetic regulation seems essential for the dynamic reprogramming of cell fate, which is correlated with local and global changes of the chromatin states that might ensure the correct spatiotemporal expression pattern of the key regulators. Future approaches might investigate in greater detail whether and how the transcriptional key regulators and the writers, erasers, and readers of epigenetic modifications interact to control DNRR.